Investigation of salicylanilide and 4-chlorophenol-based N-monosubstituted carbamates as potential inhibitors of acetyl- and butyrylcholinesterase - Krátký, Martin; Štěpánková, Šárka; Vorčáková, Katarína; Vinšová, Jarmila (Bioorganic chemistry, 2018)
Based on the presence of carbamate moiety, twenty salicylanilide N-monosubstituted carbamates concomitantly with their parent salicylanilides and five newly prepared 4-chlorophenyl carbamates obtained from isocyanates were investigated using Ellman's method for their in vitro inhibitory activity against acetylcholinesterase (AChE) from electric eel and butyrylcholinesterase (BChE) from equine serum. The carbamates and salicylanilides exhibited mostly a moderate inhibition of both cholinesterase enzymes with IC50 values ranging from 5 to 235 µM. IC50 values for AChE were in a narrower concentration range when compared to BChE, but many of the compounds produced a balanced inhibition of both cholinesterases. The derivatives were comparable or superior to rivastigmine for AChE inhibition, but only a few of carbamates also for BChE. Several structure-activity relationships were identified, e.g., N-phenethylcarbamates produce clearly favourable BChE inhibition. The compounds also share convenient physicochemical properties for CNS penetration.
Keywords: Inhibitory Concentration 50; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Electrophorus; Horses; inhibiční koncentrace 50; koně; zvířata; cholinesterasové inhibitory; butyrylcholinesterasa; chlorfenoly; Chlorophenols; Acetylcholinesterase; salicylanilidy; Salicylanilides; Animals; karbamáty; Carbamates; Butyrylcholinesterase; acetylcholinesterasa; Cholinesterase Inhibitors